Thermal Analysis on Water-Simple Rankine Cycle and Combined Cycle for Waste Heat Recovery Flat Glass Factory - Zefanya Hiro Wibowo; Budi Utomo Kukuh Widodo; Djatmiko Ichsani (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
One of the most important processes in glass production is the furnace section. The furnace’s waste heat, which still has a temperature around 400oC-500°C, is often released directly to the surrounding using a stack. Waste Heat Recovery Generation (WHRPG) and Organic Rankine Cycle (ORC) is one of the many waste heat reusing schemes implemented to increase the efficiency of industrial processes by converting the waste heat into electricity. Two schemes of the system will be studied in this research; there are Water-Simple Rankine Cycle (WSRC) and combined cycle (WSRC and ORC). In the WSRC, steam mass flow rate varied and found the highest performance to compare with combined cycle system. For combined cycle, the variations of the system are steam mass flow rate, the evaporating temperature, flue gas temperature in stack and refrigerant as working fluid. For the result, the highest combined cycle perform is 5.89 MW with steam mass flow rate 5 kg/s. Higher evaporating temperature (160°C) results in a higher combined cycle performance (5.96 MW), while, similarly, a lower flue gas temperature (120°C) also yields a higher combined cycle performance (6.3 MW). By varying the working fluids of R-11, R-113, and R-114.